The Nutritional Status Level, VO2 Max, and Basic Futsal Techniques At Geral FC Makassar - Ridwan, Andi; Ihsan, Andi; Adil, Ahmad (Sains Global Institut, Indonesia, 2023)
This study aims to determine the nutritional status, endurance, and cardiovascular of basic futsal techniques in Geral FC Makassar players. This study is descriptive of nutritional status, endurance, and basic futsal techniques. The population in this study is Geral Fc Futsal Club players with a sample of 20 players and sampling using total sampling or sampling techniques with certain considerations. The data analysis technique used is descriptive Percentage. Based on the results of data analysis, shows that nutritional status data with cardiovascular endurance against basic futsal techniques at Club Geral FC Makassar. Based on BMI classification: Low 7 people = 30%, Standard 11 people = 60%, Overweight 2 people = 10%, Obesity 0 people = 0%, Nutritional status obtained total average value (mean) 21.51, minimum data 17.91, maximum data 26.79, with a range of 87.88 and standard deviation 2.42 while clarification of cardiovascular endurance: VO2 Max ability category Very low 1 person, less 6 people, good 12 people and very good 1 person, The total mean value was 45.37, the minimum data was 39.55, the maximum data was 57.10 with a range of 17.55 and the standard deviation was 4.25. Then the results of futsal playing data analysis can be found that the skill level of 0 people (0%) is declared very good, 3 people (15%) are declared Good, 10 people (50%) are declared Sufficient, 5 people (25%) are declared Less and 2 people (10%) are declared Less once, obtained the lowest total average value (minimum) 60, the highest score (maximum) 101, the average (mean) 65.50, standard deviation (SD) 9.76